Integração entre os Sistemas de Informação Portel e WebCrm : aplicação prática no Fátima Hotels Group - Carvalho, Daniel Teófilo Cruz (2017)
Internship Report presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence